The Impact of the Real Effective Exchange Rate on Poland’s Food and Live Animal Exports - Yılmaz Toktaş; Agnieszka Parlinska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
In this study, for the 2012M1-2020M1 period, the relationship between Poland’s real effective exchange rate and its food and animal exports were examined by the bounds test. The stationary analyses of variables were examined by the ADF and PP tests. According to the results of a cointegration test, a cointegration relation among the real effective exchange rate, food and live animal exports, as well as industrial production was determined. It was also concluded that the real effective exchange rate has a long-term negative impact on Poland's food and live animal exports. This research also established that a 1% increase in the real effective exchange rate in the long-term would decrease Poland's food and animal exports by 3.091%. Also, industrial production has a positive impact on Poland’s food and animal exports, as expected. It was determined that a 1% increase in industrial production would increase Poland’s food and animal exports by 2.803%. On the other hand, the error correction term coefficient was found to be -0.119, indicating that 11% of the imbalance in the short-term will be recovered in the next period.